Formulasi Brownies Kukus Dengan Penambahan Tepung Jantung Pisang Kepok Sebagai Snack Pada Ibu Menyusui - Ahmaliah, Muslikhatin; Yuniarti, Hana; Susyani, Susyani; Terati, Terati; Mardiana, Mardiana (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2022)
Background: The success of breastfeeding mothers is largely determined by a good diet during pregnancy and after giving birth. Consumption of nutritious and balanced food is one way to increase milk production in terms of quality and quantity. Purpose: to determine the nutritional content and acceptability of the steamed brownie formulation with the addition of kepok banana flower flour as a snack for nursing mothers. Methods: The research used was experimental using a non-factorial Completely Randomized Design (CRD) with 4 treatments. The panelists of this study were 30 students of Nutrition Poltekkes Kemenkes Palembang. Results: Based on the results of the organoleptic test (taste, texture, aroma, and color) it showed that the acceptance of the preferred kepok banana heart flour brownies was F2 both in terms of color, texture and taste. with an average value of 4.60, 3.95 and 4.37. As for the aroma, the panelists chose F3 with an average value of 4.53. The nutritional content of kepok banana heart flour brownies per 100 g contains 382.64 Kcal of Energy, 6.88 g of Protein, 20.72 g of Fat, 42.16 g of carbohydrates. Conclusion: Based on the results of the study, it can be concluded that the steamed brownies with banana heart flour have met the requirements as a processed snack product and can be an alternative food supplement for breastfeeding mothers.